Modeling Relationships between Salesperson Emotional Intelligence and Customer Loyalty through Mediation of Salesperson Performance and Customer Value Co-Creation Behavior - Naser Asgari; Hamed Heidari; Seyed Mostafa Shakerian; Maryam Moazami Goudarzi (مطالعات منابع انسانی, 2020)
Background & Purpose: The ability to interact with customers effectively requires the identification of mental states and persuasion skill that can improve sales performance. This study aimed to explain the relationships between salesperson emotional intelligence and customer loyalty through the mediation of salesperson performance and customer value co-creation behavior. Methodology: This is an applied descriptive-correlational study, in which the statistical population included the salespersons working at 10 shopping centers in Tehran. The convenience sampling method was employed to select the statistical sample, whereas a questionnaire was used as the data collection tool. The path analysis model was then used through structural equation modeling (SEM) for hypothesis testing in AMOS. Findings: There were significant relationships between salesperson emotional intelligence and salesperson performance, between salesperson performance and customer loyalty, between salesperson emotional intelligence and customer value co-creation behavior, between customer value co-creation behavior and customer loyalty, and between salesperson emotional intelligence and customer loyalty through the mediation of salesperson performance and customer value co-creation behavior. Conclusion: Managers of shopping centers can enhance their salespeople’s emotional intelligence to improve customer loyalty by increasing salesperson performance and customer value co-creation behavior so that they can compete successfully with other shopping centers.